(untitled) (Global Journal of Medical Research, 2023)
In knees of patients over 50 years old with moderate varus femoro-tibial angle up to 4 of varus the medial complex ligamentopraxia technique medial collateral ligament and posterior oblique ligament was used in association with the specific treatment of medial meniscal and chondral injuries The objective was to improve the femoro-tibial conflict favoring functional rehabilitation in knees with misalignment in their anatomical axis The Lyscholm scale score was used ranging between pre and pos toperative from 31 56 to 94 31 points This tec hnique is unprecedented and its effectiveness and replicability should be observed in new studies